Pengaruh Soft Skill, Pengalaman Magang dan Pengalaman Organisasi Terhadap Kesiapan Kerja Mahasiswa dalam Perspektif Manajemen Sumber Daya Insani: Studi pada Mahasiswa di Kota Bandar Lampung - Gilang Sri Khadaffi; Is Susanto; Alief Rakhman Setyanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the influence of soft skills, internship experience and organizational experience on student job readiness in the city of Bandar Lampung. The background of this study is based on the increasing unemployment of college graduates, which shows that high education does not fully guarantee the readiness of individuals to enter the workforce. Job readiness is not only determined by academic ability, but also influenced by nontechnical skills and practical experience gained during the lecture period. Therefore, the development of soft skills, involvement in internship activities, and participation in organizations are important factors in preparing students for an increasingly competitive world of work. This study uses a quantitative approach with a survey method of 384 respondents. The research instrument was tested for validity and reliability, followed by classical assumptions such as normality, multicollinearity and heteroscedasticity. Data analysis was carried out by multiple linear regression to test the influence of independent variables on dependent variables. The results of the study show that three variables have a significant effect on job readiness. Soft skills (β=5,433), while internship experience (β=6,058), and organizational experience (β=10,412). The F test showed that the three variables had a significant effect simultaneously (F-Statistic = 1283.825, Prob (F-statistic) 0.000), with a determination coefficient (R2) of 90.40%.